THE ATTITUDINAL MEANING BUILT BY KONDE.CO REGARDING THE RATIFICATION OF CHEMICAL CASTRATION PENALTY - Hidayatul Mahmudah; Harni Kartika Ningsih (Universitas Islam Sumatera Utara (UISU), 2021)
The rise of sexual violence against women and children encourages the government to establish Government Regulation (Peraturan Pemerintah) hereafter (PP) number 70 of 2020, which contains the application of the chemical castration penalty for the offenders of sexual violence. This regulation causes pros and cons from the various parties, including women and children's observer community, selected in this case Konde.co. This study aims to discuss the attitude or position built by Konde.co toward the Government Regulation (PP) ratification concerning the chemical castration penalty for the sexual violence offenders. This research uses a qualitative approach, especially discourse analysis. The discourse analysis in this research uses the appraisal theory, which studies the attitudesystem explicitly The result of this research shows that the attitude that appears in the text is generally negative. Furthermore, the attitude aspect with the highest frequency is negative judgement.The negative attitude refers to the incompatibility and inability of the chemical castration penalty in overcoming the sexual violence problem in Indonesia. The chemical castration penalty has negative impacts, such as exacerbating sexual violence in Indonesia in the future, disturbing, like an inclement regulation, and violating human rights. The positive attitude refers to the PP’s capacity for the chemical castration penalty of the sexual violence offenders in upholding the rights of the underprivileged. Other priorities that Konde.co considers more critical in overcoming the sexual violence problem are the recovery of the victims and the immediate ratification of the Bill on the Elimination of Sexual Violence.